FENOMENA KONVERGENSI: POLA SPASIAL PADA PEMBAURAN AKTOR DI KAWASAN TEBUIRENG, JOMBANG - Hanifa Fijriah Wasnadi; Evawani Ellisa; Dic Fla Vidya Kriss Tanny; Nia Namirah Hanum (RUSTIC, 2022)
In the development of civilization, humans have become the core in urban spaces. Therefore, human encounters in urban space becomes inevitable. Simultaneously, inclusiveness has been and is still a parameter for the accomplishment of a good public spaces. This study aims to understand the spatial pattern of human encounters in urban spaces. Tebuireng’s Pesantren area and Gus Dur Tomb were then chosen as a case study due to their intense use by more than 1 million people which are divided into 3 main actors, namely santri, pilgrims and local residents. The approach used in this research is a qualitative approach, by conducting literature studies, field observations, interviews, documentation, mapping and drawing. The author finds collision or convergence phenomenon in the mixing of actors in the observed area. There are two major types of convergence that occur in the 6 major collision zones, namely single directional convergence and multi directional convergence. The convergence mechanism of each zone is then analyzed according to its type. The study found that convergence phenomenon produces swelling space as an area that holds mass overflow after the collision occurs.